2012
DOI: 10.1136/jclinpath-2011-200647
|View full text |Cite
|
Sign up to set email alerts
|

Significance of acquired diverticular disease of the vermiform appendix: a marker of regional neoplasms?

Abstract: DA has significance as a putative marker of local/regional neoplasms. Therefore, a DA specimen proved significantly more likely to harbour a neoplastic growth than a non-DA counterpart. Submission for microscopy of the entire DA specimen, whether transmural or only incipient, and a comment in the pathology report on the occasional concurrence of local/regional neoplasms in this setting seem appropriate. The observation of DA may thus provide a valuable contribution in the diagnostic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 16 publications
1
40
0
1
Order By: Relevance
“…4,18 In the current study, there were only 2 cases of appendiceal neoplasm-goblet cell carcinoid and conventional carcinoid-and a serrated polyp among the 24 diverticula cases. The low incidence of coexisting appendiceal neoplasm in our study in comparison with other published reports may be a result of selection bias, especially the exclusion of low-grade mucinous neoplasms.…”
Section: Discussionmentioning
confidence: 78%
“…4,18 In the current study, there were only 2 cases of appendiceal neoplasm-goblet cell carcinoid and conventional carcinoid-and a serrated polyp among the 24 diverticula cases. The low incidence of coexisting appendiceal neoplasm in our study in comparison with other published reports may be a result of selection bias, especially the exclusion of low-grade mucinous neoplasms.…”
Section: Discussionmentioning
confidence: 78%
“…Dupre et al reported 11 cases of neoplasia on a series of 23 patients with appendiceal diverticula (47.8% of total). Kallenback et al [20] demonstrated a similar association between appendiceal diverticula and neoplasms (43.6%; 17 cases on a series of 39 patients) while Marcacuzco et al had a lower incidence (7.1%; 3 cases on a series of 42 patients) [21]. It is recommended to execute an accurate evaluation of the appendiceal specimen when diverticula are evidenced in order to exclude possible concomitant neoplastic disease [18], [22], [23], [24].…”
Section: Discussionmentioning
confidence: 93%
“…Diverticulitis of appendix is a rare disease and reported in approximately 0.004%–2% of appendicectomies [1], [2], [3]. It is a rare clinical entity and the clinical significance of it is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare clinical entity and the clinical significance of it is unknown. Diverticulosis of appendix was first described by Kelynack in 1893 [2] and can be congenital or acquired. The congenital type is however very rare and contains all layers of the bowel wall.…”
Section: Discussionmentioning
confidence: 99%